Evaluation of National Standards for Exposure to Chemical Materials and Dusts in the State Company for Drugs Industry in Samarra - yaas, Marghoob; Khalifa, mohammed (Iraqi National Journal of Nursing Specialties, 2012)
Objective: Evaluation the national standards for exposure to chemical materials and dusts in The State Company for Drugs Industry in Samarra. Methodology: A descriptive evaluation design is employed through the present study from 25th May 2011 to 30th November 2011 in order to evaluate the national standards for exposure chemical materials and dusts in The State Company for Drugs Industry in Samarra. A purposive (non-probability) sample is selected for the study which includes (110) workers from the State Company for Drugs Industry in Samarra. Data were gathered through the workers` interviewed according to the nature of work that they perform. The evaluation questionnaire comprised of three parts which include the workers` demographic characteristic and other two part which concern the national standards for exposure to chemical materials and dusts in workplace. Reliability and validity of this tool is determined through application of a pilot study and panel of experts. Data were analyzed through the application of descriptive statistical (frequencies and percentages) and inferential statistical (mean of score). Results: The findings of the study present that the national standards for exposure chemical materials and standards for exposure to dusts that are applicable in the workplace, can be adopted as national standards. So, there is no significant impact of occupational hazards that may affect workers and work environment as a result of applicable of this standards. Recommendations: The study recommends that increase awareness, training and health education programs should be provided for all workers regularly and periodically in order to help them comply with standards for exposure chemical materials and standards for exposure to dusts in order to avoid hazards that affecting their health and work environment.